Interval between defoliation and fertilization of Panicum maximum cultivars - A. M. Motta; L. G. Mota; K. K. Melo; P. R. Silva; A. R. M. Santos; L. J. M. Motta; C. H. A. Cabral; C. E. A. Cabral (Boletim de Indústria Animal, 2021)
Forage is a low-cost food for cattle production. To achieve maximum economic and productive efficiency, nitrogen dose must be adjusted as well as the ideal time to carry out the application. Thereby, this work aimed to identify the appropriate moment to realize nitrogen maintenance fertilization on cultivars of Panicum maximum (syn. Megathyrsus maximus): BRS Tamani e MG 12 Paredão. Two experiments were carried out in a greenhouse. The first experiment (Experiment 1) at Federal University of Mato Grosso, Cuiabá, and the second experiment (Experiment 2) at Federal University of Rondonópolis. Treatments consisted of five intervals between forage defoliation and nitrogen fertilization: 0, 2, 4, 6, and 8 days. Harvests were done when Tamani and MG 12 Paredão guinea grass reached 30 + 0.70 and 78 + 0.70 cm, respectively. The intervals between forage defoliation and nitrogen fertilization did not influence the development of MG 12 Paredão, except for tiller number. In contrast, the intervals between forage defoliation and nitrogen fertilization of BRS Tamani changed the leaf number, tiller number, dry mass of each leaf blade, dry mass of each tiller, leaf blade dry mass, stem dry mass and shoot dry mass. The longer the interval between defoliation and nitrogen fertilization on BRS Tamani, the greater the decrease in development, which impacted negatively on forage mass. There was no common biological response for both cultivars, even belonging to the same species, therefore, MG 12 Paredão has flexibility for fertilization timing, while BRS Tamani fertilization should be performed as close as possible to defoliation.